2016
DOI: 10.6018/eglobal.15.4.259361
|View full text |Cite
|
Sign up to set email alerts
|

El método buttonhole como técnica de punción de la fístula arteriovenosa en hemodiálisis: Una revisión de la literatura

Abstract: Nº 44 Octubre 2016Página 341 REVISIONESEl método buttonhole como técnica de punción de la fístula arteriovenosa en hemodiálisis: Una revisión de la literatura RESUMENIntroducción: La hemodiálisis es el tratamiento de elección en los pacientes con insuficiencia renal crónica. La clave para un tratamiento adecuado es tener un buen acceso vascular. Por ello, las fístulas arteriovenosas son consideradas la mejor opción. Uno de los principales factores que influyen en la supervivencia de estas es la técnica de pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The database search identified nine reviews that included literature searches performed systematically. 6,16,17,[25][26][27][28][29][30] Search of the content and reference lists of these sources identified three trials not identified in the database search. [31][32][33] None of these trials could be sourced from the references provided and no author contact details were provided.…”
Section: Search Resultsmentioning
confidence: 99%
“…The database search identified nine reviews that included literature searches performed systematically. 6,16,17,[25][26][27][28][29][30] Search of the content and reference lists of these sources identified three trials not identified in the database search. [31][32][33] None of these trials could be sourced from the references provided and no author contact details were provided.…”
Section: Search Resultsmentioning
confidence: 99%